Pengaruh Model Pembelajaran Superitem terhadap Kemampuan Penalaran Matematis Siswa Kelas X IPA SMAN 1 Lembah Melintang Tahun Pelajaran 2021/2022 - Rodiatun Ulsiyah DN; Aniswita Aniswita (Journal on Education, 2023)
This study uses the Superitem learning model learning model. The formulation of the research problem is "Is there any influence of the Superitem learning model on students' mathematical reasoning abilities in class X IPA SMAN 1 Lembah Melintang for the 2021/2022 academic year". The aim is to find out whether there is an effect of the Superitem learning model on students' mathematical reasoning abilities in class X IPA SMAN 1 Lembah Melintang for the 2021/2022 academic year. The hypothesis of this study "There is a significant influence of the Superitem learning model on students' mathematical reasoning abilities in class X IPA SMAN 1 Lembah Melintang for the 2021/2022 academic year." This research is an experimental type by designing the static group comparison. The research population was all students of class X IPA SMAN 1 Lembah Melintang and the samples were class X IPA 1 and X IPA 2. The instruments used in this study included mathematical reasoning ability tests. The data analysis technique used is t test and Minitab Software. Based on the results of the analysis, tcount = 2.62 and ttable = 1.672. Because 2.62> 1.672, the conclusion is that H0 is rejected and H1 is accepted. The conclusion is that the mathematical reasoning abilities of students who take part in learning using the Superitem learning model are better than students who take conventional learning in class X IPA SMAN 1 Lembah Melintang for the 2021/2022 academic year.